Impact of Bilateral Sympathetic Stellate Ganglionectomy on TGF-β1 Signaling Pathway in Rats With Chronic Volume Overload - Zhang, Mingjing; Liu, Xiaogang; Wu, Jie; Yu, Yijun; Wang, Yuting; Gu, Ye (Frontiers in Physiology, 2020)
Abstract Background We previously reported that bilateral sympathetic stellate ganglionectomy attenuated cardiac remodeling and fibrosis in rats with chronic volume overload. Transforming growth factor beta 1 (TGF-β1) is a polypeptide member of the transforming growth factor beta superfamily of cytokines and actively involved in many pathological processes of cardiovascular diseases. Present study explored the impact of bilateral sympathetic stellate ganglionectomy on TGF-β1 pathway in this model. Methods and Results Male Sprague-Dawley rats were randomly divided into sham (S) group, abdominal aorta-cava fistula (AV) group and bilateral sympathetic stellate ganglionectomy after abdominal aorta-cava fistula (AD) group. 12 weeks after the abdominal aorta-cava fistula surgery, myocardial expression of norepinephrine (NE) and hydroxyproline were significantly higher, while acetylcholine was downregulated in AV group compared to S group, above changes were partly reversed in AD group. Myocardial expression of TGF-β1 and activity of Smad2/3 phosphorylation were also upregulated in AV group compared to S group, which could be reversed by bilateral sympathetic stellate ganglionectomy. In vitro, the TGF-β1 expression in cultured myocardial fibroblasts and the proliferation of myocardial fibroblasts were significantly increased post stimulation with NE in a dose-dependent manner and these effects could be blunted by co-treatment with TGF-β1 inhibitor. Conclusions Our study results indicate that stellate ganglionectomy decreases cardiac norepinephrine release, which leads to decreased TGF-β1 release and reduced fibrosis in rats with chronic volume overload.